Relation between thyroid hormonal status, neutrophillymphocyte ratio and left ventricular systolic function in patients with acute coronary syndrome - Mirela Halilčević; Edin Begić; Amela Džubur; Alen Džubur; Buena Aziri; Azra Durak-Nalbantić; Alden Begić; Ammar Brkić; Ena Gogić; Orhan Lepara (Medicinski glasnik, 2022)
Aim: To examine a relation of thyroid function, neutrophil-lymphocyte ratio (NLR) with left ventricular function measured through the left ventricular ejection fraction (LVEF) in patients with acute myocardial infarction treated with percutaneous coronary intervention (PCI). Methods: This prospective research involved 160 consecutive patients with acute myocardial infarction. Patients were divided into those with normal thyroid hormone status (n=80) and those with hypothyroidism (newly diagnosed) (n=80). Inflammatory parameters and parameters of hormonal status were taken for analysis: thyroid-stimulating hormone (TSH), thyroxine (T4), triiodothyronine (T3), free thyroxine (FT4), and free triiodothyronine (FT3). All patients underwent transthoracic echocardiographic examination (TTE) five days upon admission, and left ventricular ejection fraction (LVEF) was analysed. Results: Significant difference between the two groups was verified in values of T3, T4, erythrocytes, haemoglobin, haematocrit, neutrophil, lymphocytes, NLR, C-reactive protein (CRP) and sedimentation rate. Patients with euthyroidism had a higher frequency of coronary single-vessel disease (p=0.035) and a significantly lower frequency of triple vessel disease (p=0.046), as well as a higher median value of LVEF (p=0.003). There was a significant correlation between LVEF with haemoglobin values (p=0.002), NLR (p=0.001), and CRP (p=001). Conclusion: The altered status of the thyroid gland in acute myocardial infarction is associated with the severity of the coronary blood vessel lesion, LVEF and correlates with inflammatory response.
Keywords: myocardial infarction; prognosis; risk